The Semantic Space of Social Networks: Book Review of "Networks 4.0. Complexity Management" / ed. by A.N. Raskhodchikov. Moscow: VCIOM, Social Research Agency "Stolitsa", 2020. 132 p - Aleksei I. Shcherbinin (Peoples' Friendship University of Russia (RUDN University), 2020)
-